Analysis of Occupational Safety, Health and Accident on Work Productivity in the Pamong Praja Police Unit, Labuhanbatu Regency - Marsum, Marsum; Zebua, Yuniman; Pitriyani, Pitriyani (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study aims to analyzesafety, health, and work accidents on the work productivity of the Civil Service Police Unit of Labuhanbatu Regency. This type of research is quantitative, the place of this research is the Civil Service Police Unit on Jalan. WR. Supratman No. 46, Labuhanbatu. Data collection techniques used in the study were observation, documentation and questionnaires using a Likert scale. The population in this study were 233 employees of the Civil Service Police Unit of Labuhanbatu Regency. The sample was taken using the Slovin formula, which was determined with a significance level of 0.05, so the sample size in this study was 147 people. The multiple linear regression equation from this research is: Y=0.914+01875X1+0.367X2+0.516X3. The value of B on safety (B1) is 0.187. The health value (B2) is 0.367. The work accident value (B3) is 0.516 and the constant value (a) is 0.914. The description of the multiple linear regression equation shows that the variables of safety (X1), health (X2), and work accidents (X3) have a positive direction coefficient on work productivity. The t-count value of 3.006 > t-table of 1.655 proves that the safety variable (X1) has a positive effect on the work productivity variable (Y). Then the significant value is 0.003 <0.05, which means the safety variable (X1) has a significant effect on the work productivity variable (Y). Based on the results of the regression analysis, the t-count value was 5.090 > t-table 1.655, which means that the health variable (X2) has a positive effect on the work productivity variable (Y). Then the significant value is 0.00o <0.05, which means that the health variable (X2) has a significant effect on the work productivity variable (Y). Furthermore, the results of the regression analysis obtained the t arithmetic value of 6.316 > t table 1.655 proving that the work accident variable (X3) has a positive effect on the work productivity variable (Y). Then the significant value is 0.000 <0.05 indicating that the work accident variable (X3) has a significant effect on the work productivity variable (Y). The value of Fcount is 104,734 > Ftable 2.67 with a significance value of 0.000 < 0.05. From the results of this study, it can be concluded that safety (X1), health (X2), and work accidents (X3) simultaneously have a positive and significant effect on work productivity (Y).